(untitled) (Research, Society and Development, 2022)
This article is a systematic review whose objective was to analyze the main changes in habits and social impacts of sex workers in the context of the COVID-19 pandemic. The texts belonging to Pubmed, Web of Science (all databases), Embase, Scopus and Cochrane Library were reviewed without distinction as to language or year of publication, only articles referring to women of legal age as their population were analyzed. Of the 89 documents retrieved, 29 met our inclusion and exclusion criteria. From the qualitative analysis of the findings, it is possible to identify the sex workers as a population at risk and that was not properly supported. In this way, it is possible to observe that the inclusion of prostitutes in the planning of public policies must be thought of in order to guarantee the basic rights of these professionals.